New Insight Into Pathogenicity and Secondary Metabolism of the Plant Pathogen Penicillium expansum Through Deletion of the Epigenetic Reader SntB - Tannous, Joanna; Barda, Omer; Luciano-Rosario, Dianiris; Prusky, Dov B.; Sionov, Edward; Keller, Nancy P. (Frontiers in Microbiology, 2020)
Penicillium expansum is one of the most harmful postharvest pathogens of pomaceous fruits and the causal agent of blue rot disease. During infection, P. expansum produces the toxic secondary metabolites patulin and citrinin that can impact virulence and, further, render the fruit inedible. Several studies have shown that epigenetic machinery controls synthesis of secondary metabolites in fungi. In this regard, the epigenetic reader, SntB, has been reported to govern the production of multiple toxins in Aspergillus species, and impact virulence of plant pathogenic fungi. Here we show that deletion of sntB in P. expansum results in several phenotypic changes in the fungus including stunted vegetative growth, reduced conidiation, but enhanced germination rates as well as decreased virulence on Golden Delicious apples. In addition, significant alteration of the metabolic profile was observed in the ΔsntB mutant, with a decrease in both patulin and citrinin biosynthesis in vitro and patulin in apples. SntB positively regulates expression of three global regulators of virulence and secondary metabolism (LaeA, CreA and PacC) which may explain in part some of the phenotypic and virulence defects of the ΔsntB strain. Lastly, results from this study revealed that the controlled environmental factors (low temperatures and high CO2 levels) to which P. expansum is commonly exposed during fruit storage, resulted in a significant reduction of sntB expression and consequent patulin and citrinin reduction. These data identify the epigenetic reader SntB as critical factor regulated in postharvest pathogens under storage conditions and a potential target to control fungal colonization and decaying of stored fruit.